ABL1-Directed Inhibitors for CML: Efficacy, Resistance and Future Perspectives - MASSIMINO, MICHELE; STELLA, STEFANIA; TIRRÒ, ELENA; PENNISI, MARIA STELLA; VITALE, SILVIA RITA; PUMA, ADRIANA; ROMANO, CHIARA; DI GREGORIO, SANDRA; TOMARCHIO, CRISTINA; DI RAIMONDO, FRANCESCO; MANZELLA, LIVIA (Anticancer research, 2020)
The introduction of tyrosine kinase inhibitors (TKIs) directed against the catalytic activity of the ABL tyrosine kinase has considerably improved the outcome of chronic myeloid leukemia (CML) patients in the chronic phase of the disease. Indeed, these individuals currently show a life-expectancy comparable to those of healthy subjects. Currently, five TKIs (imatinib, dasatinib, nilotinib, bosutinib and ponatinib) are approved for the treatment of CML and can be used as first, second or further lines of treatment according to disease risk scores, patient comorbidities and the presence of known TKI resistance mechanisms. In fact, 15-20% of all CML patients fail to achieve optimal responses according to the current definitions of the European Leukemia Network and will require sequential TKI treatment to avoid disease progression. In this review, we present the state of art in several crucial areas of CML management by briefly: i) depicting the domain structure of the BCR-ABL1 oncoprotein; ii) describing pivotal data concerning TKI efficacy; iii) illustrating the diverse molecular mechanisms causing TKI resistance; and iv) summarizing new ABL1-directed therapeutic approaches that are presently under investigation.